New strategies and findings for behavioral interventions in autism spectrum disorders. (November 2013) - Lord, Catherine; Jones, Rebecca M.
Abstract : Behavioral interventions are the major source of change for children with autism spectrum disorders and a major cost to families and government. In the last 5 years, a number of carefully designed intervention studies have provided new information about the effects of caregiver training and direct instruction on behavior treatments. Outcomes of these interventions are neither easily assessed nor simple, but are dependent on child characteristics as well as caregiver skills and attitudes. Some interventions aimed at specific skills have similar results, yet there is growing evidence that child interventions may have different effects than caregiver training, although both may affect outcomes in the long term. New research strategies and findings are discussed, with a focus on how underlying behaviors and specific components may contribute to intervention outcomes.